2023
DOI: 10.1101/2023.03.09.531878
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular diversity of bivalve transmissible neoplasia of blue mussels in the Kola Bay (Barents Sea) indicates a recent migration of the cancer lineages between the North Pacific and Northern Europe

Abstract: Bivalve transmissible neoplasia (BTN) is a leukemia-like cancer "metastasizing" by transmission of living cancer cells between molluscs. Blue mussels harbor two evolutionary lineages of BTN,MtrBTN1 andMtrBTN2, both derived fromMytilus trossulus. WhileMtrBTN1 has been found only inM. trossulusin North Pacific,MtrBTN2 parasitizes different Mytilus species worldwide, particularly in Western Europe. No targeted studies of BTN in Northern European mussels (M. edulis,M. trossulus) have been made. We searched for BTN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
(205 reference statements)
0
1
0
Order By: Relevance
“…The cancers arise from normal cockles, so this is to be expected, but it highlights the difficulty in relying on a single qPCR marker. Recently, a similar study found that an EF1-α allele previously only found in the Mytilus trossulus BTN (MtrBTN1) is also present in the germline of non-neoplastic animals in Northern Europe (23,24). This suggests that the cancer may have arisen from the Northern Europe mussel population, but also renders that marker nonspecific in animals with that allele.…”
Section: Discussionmentioning
confidence: 91%
“…The cancers arise from normal cockles, so this is to be expected, but it highlights the difficulty in relying on a single qPCR marker. Recently, a similar study found that an EF1-α allele previously only found in the Mytilus trossulus BTN (MtrBTN1) is also present in the germline of non-neoplastic animals in Northern Europe (23,24). This suggests that the cancer may have arisen from the Northern Europe mussel population, but also renders that marker nonspecific in animals with that allele.…”
Section: Discussionmentioning
confidence: 91%